Essential oil composition of Alseodaphne perakensis (Gamble) Kosterm from Malaysia. Issue 3 (1st February 2021) - Anuar, Muhammad Zul Afiq; Salleh, Wan Mohd Nuzul Hakimi Wan; Khamis, Shamsul; Nafiah, Mohd Azlan; Mat Said, Zahid
Abstract: The chemical composition of the essential oil from the leaves of Alseodaphne perakensis (Gamble) Kosterm (Lauraceae) growing in Perak, Malaysia was investigated for the first time. The essential oil was obtained by hydrodistillation and fully characterized by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). A total of 37 components (90.9 ± 2.5%) were successfully identified in the essential oil which were characterized by high proportions of bicyclogermacrene (15.8 ± 0.5%), δ-cadinene (11.7 ± 0.2%), γ-cadinene (6.3 ± 0.4%), and aromadendrene (5.6 ± 0.5%). Abstract :